2012
DOI: 10.5088/atl.2012.34.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Fertilização Orgânica Com Carbono No Cultivo Intensivo Em Viveiros Com Sistema De Bioflocos Do Camarão Branco Litopenaeus Vannamei

Abstract: peso médio inicial de 0,112 ± 0,07g foram cultivados na densidade de 85 camarões m-2 em 6 viveiros escavados (500 m² cada) e revestidos com PEAD (geomembrana). No tratamento com fertilização de carbono não houve renovação da água de cultivo. No tratamento controle os camarões foram cultivados sem adição extra de carbono, e renovação de água foi de 10 % por semana. Não houve diferença significativa entre os parâmetros de qualidade de água (p>0,05). A sobrevivência e conversão alimentar não apresentaram diferenç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
2
1
0
1
Order By: Relevance
“…According to Fróes et al (2012) and Schveitzer et al (2013a), the addition of sugarcane molasses as an external source of carbon to the ASS favors the transition from an autotrophic to a heterotrophic medium and the control of nitrogen compounds in the system, which is in agreement to the findings of this work. Avnimelech (1999) and that of ammoniacal nitrogen was lower than the detection limit of the method (5.0 mg N-NH 3 .L -1 ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…According to Fróes et al (2012) and Schveitzer et al (2013a), the addition of sugarcane molasses as an external source of carbon to the ASS favors the transition from an autotrophic to a heterotrophic medium and the control of nitrogen compounds in the system, which is in agreement to the findings of this work. Avnimelech (1999) and that of ammoniacal nitrogen was lower than the detection limit of the method (5.0 mg N-NH 3 .L -1 ).…”
Section: Resultssupporting
confidence: 89%
“…After the shrimp farming wastewater was supplemented with molasses and nutrients at a ratio of 100C:5N:1P, as suggested in the literature (RATSAK; MAARSEN; KOOIJMAN, 1996;KARAMALIDIS et al, 2010;WIJEKOON;VISVANATHAN;ABEYNAYAKA, 2011;SHAHI et al, 2016), the value of COD increased to 1,170±430 mg O 2 .L -1 , and the concentration of TSS increased to 323±128 mg.L -1 , thus, reaching adequate levels for the growth of a heterotrophic community (AVNIMELECH, 1999). This increase in the concentration of TSS positively affected the system because, as reported by Fróes et al (2012) and Schveitzer et al (2013b), the removal of ammonia is hindered when the concentration of TSS is lower than 200 mg.L -1 due to slow nitrification by autotrophic bacteria.…”
Section: Resultsmentioning
confidence: 76%
“…The results of the present study were higher than those reported by Sareban et al (2013), in which two cycles per year had yields ranging from 4000 to 5625 kg ha −1 cycle −1 . Similar results were obtained by Fróes et al (2012) that found a yield of 6759 kg ha −1 cycle −1 in lined ponds without organic carbon fertilization. Similarly, Sookying et al (2011) obtained a yield of 6149 kg ha −1 cycle −1 in L. vannamei ponds.…”
Section: Discussionsupporting
confidence: 90%
“…Para alcançar esta proporção, realiza-se a fertilização da água com fontes ricas em carbono orgânico, como melaço, dextrose, farelos de trigo e arroz, farinha de mandioca, entre outras (Froes et al, 2012). De acordo com Avnimelech (1999), a fonte de carbono serve como um substrato para o bioflocos.…”
Section: Compostos Nitrogenadosunclassified